Examining the Factors of Ewom That Influence the Consumers’ Online Purchase Decision in Nilai, Malaysia - Yang, Hong (2013)
Previous researchers have shown that word of mouth (WOM) has a significant impact on consumers’ purchase decision. With the development of information technology and the increasing number of Internet user, the influencing power of electronic word of mouth (eWOM) which is a new generated form of WOM has increased greatly in the consumers’ online purchase decision making process. This study is going to identify the factors of eWOM that influence the consumers’ online purchase decision. Based on the literature reviewed, a theoretical framework was developed and the researcher conducted a convenience sampling of data whereby 193 respondents were surveyed using questionnaires. The collected data was analysed using the Statistical Package for Social Science (SPSS) where reliability test, validity test and regression analysis were employed. The results showed that information quality website credibility, quantity, negative eWOM, reviewer’s expertise, receiver’s product involvement have positive effect on the consumers’ online purchase decision. While the receiver’s expertise has negative effect on the consumers’ online purchase decision.